2013
DOI: 10.1309/ajcpgkojv15avznt
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Contain Cholesterol Crystals in Transfusion-Related Acute Lung Injury (TRALI)

Abstract: The damage to the pulmonary vascular endothelium in TRALI is related to formation of cholesterol crystals originating within neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
3
0
2
Order By: Relevance
“…Numerous studies in recent years have found that lidocaine can inhibit the inflammatory reaction 4 , 8 , protect against acute lung injury 5 7 , exert a neuroprotective effect and alleviate postoperative cognitive dysfunction (POCD) 9 – 11 . There is also evidence that lidocaine may have anticancer actions in a wide range of cancer cells 12 16 , and it may have a sensitizing effect on anticancer drugs 17 , 18 . Procaine, another local anesthetic agent, has been found to attenuate the growth of MCF-7 breast cancer cells 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies in recent years have found that lidocaine can inhibit the inflammatory reaction 4 , 8 , protect against acute lung injury 5 7 , exert a neuroprotective effect and alleviate postoperative cognitive dysfunction (POCD) 9 – 11 . There is also evidence that lidocaine may have anticancer actions in a wide range of cancer cells 12 16 , and it may have a sensitizing effect on anticancer drugs 17 , 18 . Procaine, another local anesthetic agent, has been found to attenuate the growth of MCF-7 breast cancer cells 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of coagulation factors will concurrently increase, resulting in a hypercoagulable state [ 13 ]. However, when hypoproteinemia is present, water accumulates in the interstitial spaces, resulting in increased blood viscosity and a higher risk of thrombosis [ 15 ]. In the present study, a significant intergroup difference (P < 0.001) was observed, and patients with lower Alb levels had a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a significant intergroup difference (P < 0.001) was observed, and patients with lower Alb levels had a poorer prognosis. In addition, lipids, especially HDL cholesterol, play a key role in the metabolism of normal lung tissue [ 14 ], and some studies have shown that cholesterol is crucial in the inflammatory response after acute lung injury [ 15 ]. The pathogenesis of APE is often accompanied by an inflammatory response, which can affect the synthesis of cholesterol and the absorption and transport of hepatic lipids [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Fallstudien wurde dies aber bisher nicht nachgewiesen [30]. Bei 2 Patienten, die an TRALI verstorben sind, wurden in den Lungengefäßen Cholesterinkristalle gefunden [31]. Eine weitere wichtige Beobachtung ist, dass nicht alle Empfänger, die ein Blutprodukt mit leukozytären oder neutrophilen Antikörpern erhalten, auch eine TRALI entwickeln.…”
Section: Pathophysiologie !unclassified
“…In Fallstudien wurde dies aber bisher nicht nachgewiesen [30]. Bei 2 Patienten, die an TRALI verstorben sind, wurden in den Lungengefäßen Cholesterinkristalle gefunden [31].…”
unclassified